Comparing Voice Assistant Risks and Potential with Technology-Based Users: A Study from Germany and Spain - Klein, Andreas M.; Rauschenberger, Maria; Thomaschewski, J¨org; Escalona, Maria Jos´e (Journal of Web Engineering, 2021)
Currently, voice assistants (VAs) are trendy and highly available. The VA adoption rate of internet users differs among European countries and also in the global view. Due to speech intelligibility and privacy concerns, using VAs is challenging. Additionally, user experience (UX) assessment methods and VA improvement possibilities are still missing, but are urgently needed to overcome users’ concerns and increase the adoption rate. Therefore, we conducted an intercultural study of technology-based users from Germany and Spain, expecting that higher improvement potential would outweigh concerns about VAs. We investigated VA use in terms of availability versus actual use, usage patterns, concerns, and improvement proposals. Comparing Germany and Spain, our findings show that nearly the same amount of intensive VA use is found in both technology-based user groups. Despite cultural differences, further results show very similar tendencies, e.g., frequency of use, privacy concerns, and demand for VA improvements.